Financial Performance Analysis Before and After the Decline in Oil Production: Case Study in Indonesian Oil and Gas Industry - Mardawiyah Daryanto, Wiwiek; Nurfadilah, Dety (International Journal of Engineering and Technology, 2018)
Indonesiaâ€™s oil and gas industry is the huge contributor to government export revenues and foreign exchange and contributes a substantial amount to state revenue. However, the total of oil production declined around 4,41% per year since 2007, and the sharpest decline was in 2013. This situation gives impact to the performance of oil and gas industry, especially government revenues. Therefore, the purpose of this study is to measure the financial performance of Oil and Gas Industry and to examine the significance differences between the financial performance before and after the decline in oil and gas production. The data were collected from financial report and the period was divided into two periods, before the decline in production (2011 â€“ 2012) and after the decline in production (2014 â€“ 2015). Paired sample t-test and financial ratio analysis (FRA) were used to analyzed the data. The finding shows that the largest oil and gas company in Indonesia is still in good financial condition, although it gained loss. In addition, current ratio and return on equity had significance difference during the period of before and after a decline in oil and gas production. The authors believe that the findings will be helpful for managers who continuously attempt to explore opportunities to provide a higher return.Â